MEMBANGUN REVOLUSI MENTAL MELALUI DIKLAT PENDIDIKAN KARAKTER BAGI GURU PELOPOR PANCASILA DI SURAKARTA - Yusuf, Anita Trisiana & (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2018)
Various problems with the destruction of the Indonesian nation and state life institutions are increasingly approaching concerns. The emergence of grassroots movements that undermine the people of this nation is increasingly visible and shows a crisis of exemplary in the community, thus giving rise to a series of socio-cultural conflicts that occur in the midst of society in various regions. The participants in this service program are, non-productive society, civic teachers at Senior High School Teacher in Surakarta City. They are a pioneer of Pancasila Teachers who need education and training in the form of Character Development Training activities as one of the activities that will sustain and filter the problems of socio-cultural conflicts that arise in society so that peace and comfortable will be achieved in people's lives. The results of this program are as a part of this service activity in the form of Social manipulation and Models that reflect systematically arranged steps, from an activity consisting of a guide module for Character Building Training with national-scale scientific articles that will support character nation building in the framework of implementing mental revolution . While the method used in this service is CIPP stands for evaluation of the whole based on Context, Inputs, Process, and Product. The results of this service are reducing socio-cultural conflicts in the life of the Pancasila, in order to implement the Mental Revolution. Hopefully all service activities will improve and provide services, and community empowerment.Keywords: Mental Revolution, Education and Training, Character Education, Pancasila